2020
DOI: 10.1111/pai.13334
|View full text |Cite
|
Sign up to set email alerts
|

Preschool wheezing and asthma in children: A systematic review of guidelines and quality appraisal with the AGREE II instrument

Abstract: Background: Asthma-like symptoms in preschool children, such as wheezing and dyspnea, are common time-and resource-consuming diagnostic and management challenges. Quality of wheezing and asthma recommendations varies. The purpose of this study, carried out by the European Academy of Allergy and Clinical Immunology (EAACI) Task Force for Preschool Wheeze, was to systematically review and assess the quality of guidelines for diagnosis and treatment of preschool wheezing and/or asthma. Methods: The Cochrane Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(73 reference statements)
0
10
0
Order By: Relevance
“…(1) Before deciding whether infants and preschool children with asthma and preschool wheeze should be treated, it is necessary to define the type of asthma. Early identification of children presenting with features of eosinophilic/atopic inflammation should be performed, as there are many good international recommendations for the management of this type of asthma [7]. (2) Peripheral eosinophilia, allergen sensitization, evidence of specific airway microorganisms, neutrophilic features, and infection may provide important information of the patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Before deciding whether infants and preschool children with asthma and preschool wheeze should be treated, it is necessary to define the type of asthma. Early identification of children presenting with features of eosinophilic/atopic inflammation should be performed, as there are many good international recommendations for the management of this type of asthma [7]. (2) Peripheral eosinophilia, allergen sensitization, evidence of specific airway microorganisms, neutrophilic features, and infection may provide important information of the patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate to what extent 'Preschool Wheezing' coincides with putative or diagnosed asthma, which in children is often described as 'eosinophilic allergic airways disease' [6], for which good guidelines and treatment regimens exist [7]. The fact is that many children presenting with recurrent preschool wheezing develop eosinophilic asthma, and the major task is to detect during early childhood those who respond to steroid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The AGREE II scores obtained by national guidelines from the UK and the Netherlands were comparable to the ones assigned by Ruszczyński et al . to national and professional guidelines for the diagnosis and management of paediatric asthma [ 34 ]. The finding of higher scores for scope & purpose and on clarity of presentation and lower scores for editorial independence are in agreement with prior studies of local CPGs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines for prevention or treatment of these highly prevalent clinical problems are scanty [10 ]. Over the last decades, attempts have been made to reduce post‐infectious respiratory symptoms and morbidity by using inhaled corticosteroids or leukotriene receptor antagonists, but no disease‐modifying effects have been documented [11, 12 ]. It was, however, observed that living in farming communities may increase the efficiency of the immune responses, not only against allergens but possibly also against infectious pathogens [13 ].…”
Section: Introductionmentioning
confidence: 99%